Seasonal Variations of Chemical Weathering and CO2 Consumption Processes in the Headwater (Datong River Basin) of the Yellow River Draining the Tibetan Plateau - Yang, Liu; Zhang, Fei; Hu, Yadan; Zhan, Yun; Deng, Li; Huang, Huayu; Sun, Hui; Wei, Yaben; Li, Xiangliang (Frontiers in Earth Science, 2022)
The Yellow River basin covers contrasting tectonics, climate, and vegetation settings. To explore the seasonal chemical weathering differences from the upstream to downstream of the Yellow River basin, we collected weekly river waters from the Datong River draining the Tibetan Plateau in 2017. Our results show remarkably seasonal variations of major ions. A forward model was employed to quantify the contribution of silicate, carbonate, and sulfide oxidation/evaporite and atmospheric input to the cations, which yielded the contributions of 9.21 ± 1.57%, 46.07 ± 1.4%, 21.46 ± 1.03%, and 23.26 ± 1.72%, respectively, indicating a dominated carbonate weathering to the river chemistry. The significant correlation between the carbonate weathering rate and runoff suggests a critical runoff control on chemical weathering in the Datong River catchment. A comprehensive comparison between the upper and middle-lower reaches of the Yellow River basin shows a declined silicate weathering and CO2 consumption rate (ØCO2sil) from the upstream to downstream. In contrast, the physical erosion rate shows an increased trend, with the most prominent increase in the midstream Loess Plateau. A further comparison between the Yellow River draining the Tibetan Plateau and the Loess Plateau shows 4.5 times higher ØCO2sil but 9.5 times lower erosion rate. In conclusion, we propose that the runoff, rather than erosion, plays a central role on chemical weathering in the Yellow River basin, which provides insight for in-depth understanding the surficial weathering and the global carbon cycle.